Mock Board and Customs Broker Licensure Examination Performance of a Select Higher Education Institution: A Predictive-Correlational Approach - Dante Jr, Julian M; Gutierrez, Ernell Bautista; Doyo, Joan R.; Cristobal, Charito S. (Future Science / FSH-PH Publications, 2024)
Board courses have been highlighted in all higher education institutions regardless of the program. Most education institutions, if not all, are using board performance as one of their marketing strategies to attract more enrollees, and the customs administration is not an exception. Thus, this study is conducted to determine whether mock board performance is associated with licensure examination performance and if it can predict such. The study utilized thirty-six (36) takers from 2021 – 2023. Kolmogorov-Smirnov Test of 2-independent Sample is used and determined that data are normally distributed with significance values greater than 0.05. On the other hand, Spearman-Rank Correlation is used and determined that Performance in the Mock Board Examination is directly related to the Performance in the Customs Broker Licensure Examination with significance values less than 0.05. On the other hand, simple regression is used and determined that performance in the mock board examination is a determinant for the performance in the licensure examination obtaining probability values of less than 0.05.